2022
DOI: 10.1021/acs.jpcb.2c02836
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of the Tau Amyloid Fibril Core Dimer at the Surface of a Lipid Bilayer Model: I. In Alzheimer’s Disease

Abstract: A tau R3–R4 domain spanning residues 306–378 was shown to form an amyloid fibril core of a full-length tau in the brain of patients with Alzheimer’s disease. Recently, we studied the dynamics of a tau R3–R4 monomer at the surface of a lipid bilayer model and revealed deep insertion of the amino acids spanning the PHF6 motif (residues 306–311) and its flanking residues. Here, we explore the membrane-associated conformational ensemble of a tau R3–R4 dimer by means of atomistic molecular dynamics. Similar to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Interestingly, a recent MD simulation study has revealed that the PHF6 motif (V306-K311) of an R3−R4 tau dimer associated with Alzheimer's disease bears high β-sheet probability even when the dimer mostly remains in a random coil-rich state when it is absorbed on the membrane. 71 Then, the β-sheet probability of residues V309−Y310 in β1, K317−T319 in β2, V350−S352 in β6, and K375−T377 in β8 is significantly decreased in the Tau + QE system (the result for β fragments is shown in Figure S1a). Remarkably, the disruption of the β-sheet in the PHF6 motif can reduce the membrane binding, impede the protein/ phospholipid complex formation, and abrogate its uptake by primary neurons in hippocampus, thus weakening tau toxicity.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Interestingly, a recent MD simulation study has revealed that the PHF6 motif (V306-K311) of an R3−R4 tau dimer associated with Alzheimer's disease bears high β-sheet probability even when the dimer mostly remains in a random coil-rich state when it is absorbed on the membrane. 71 Then, the β-sheet probability of residues V309−Y310 in β1, K317−T319 in β2, V350−S352 in β6, and K375−T377 in β8 is significantly decreased in the Tau + QE system (the result for β fragments is shown in Figure S1a). Remarkably, the disruption of the β-sheet in the PHF6 motif can reduce the membrane binding, impede the protein/ phospholipid complex formation, and abrogate its uptake by primary neurons in hippocampus, thus weakening tau toxicity.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…The binding of Aβ to ganglioside-containing membranes also plays an important role in the pathogenesis of AD . Interactions of Aβ species and other amyloid proteins with membrane cell are very transient and oligomer-size dependent. , Helical intermediates appear to be particularly important in membrane-catalyzed amyloid formation …”
Section: Resultsmentioning
confidence: 99%
“…65 Interactions of Aβ species and other amyloid proteins with membrane cell are very transient and oligomer-size dependent. 62,[66][67][68] Helical intermediates appear to be particularly important in membrane-catalyzed amyloid formation. 69 Extending their cubic lattice to interactions of Aβ42 with hydrophilic and hydrophobic surfaces, Li et al showed that, consistent with experimental studies, an increase in roughness slows down fibril formation, and this process becomes inhibited at a very highly level of roughness.…”
Section: Protein Self-assembly Near In Vivo Conditionsmentioning
confidence: 99%
“…PHF6 lies at the beginning of the third repeat domain (R3) of tau and is believed to play a critical role in promoting tau aggregation 30−32 and the interactions of tau with the membranes. 33,34 It displays a strong self-assembling tendency to form fibrils similar to those formed by full-length tau. 35,36 Therefore, PHF6 is extensively used as a simple model system for studying tau aggregation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among them, Try-310 (Y310) has received predominant attention since it is located within the aggregation-prone hexapeptide 306 VQIVYK 311 (PHF6). PHF6 lies at the beginning of the third repeat domain (R3) of tau and is believed to play a critical role in promoting tau aggregation and the interactions of tau with the membranes. , It displays a strong self-assembling tendency to form fibrils similar to those formed by full-length tau. , Therefore, PHF6 is extensively used as a simple model system for studying tau aggregation . Recent studies demonstrated that Y310 phosphorylation could decrease the propensity of PHF6 sequence to form fibrils and delay tau aggregation. , Santa-María et al investigated the regions of tau that participate in PHF formation and found that PHF6 could fibrillize in the absence of inducers, and the phosphorylation of Y310 abolished the formation of PHF6 fibrils .…”
Section: Introductionmentioning
confidence: 99%